Determining Factors of Knowledge Management and its impact on Organizational Performance in BANI environment: A theorical review - Urbano-Carazo, María I. (EFIM Ediciones, 2022)
Organizations currently confront unstable and highly uncertain environments, in this sense, they must collect elements that allow them to increase their organizational performance in such a way that they can face these environments. That is why it is proposed to analyze the determinants of knowledge management and its impact on organizational performance in BANI environments. For such purposes, a theoretical review is proposed to elucidate the main elements of these constructs mentioned aspects such as knowledge management, knowledge creation and transfer, the competitive advantage of organizations and their interactions in unstable environments. One of the main results points to consider these elements as inputs for organizations to contribute to their strategic planning, rethink their strategic direction, their strategies and the approach to human talent and knowledge as the main intangible asset and organizational strength.